2009
DOI: 10.1084/jem.20082136
|View full text |Cite
|
Sign up to set email alerts
|

Natural micropolymorphism in human leukocyte antigens provides a basis for genetic control of antigen recognition

Abstract: Human leukocyte antigen (HLA) gene polymorphism plays a critical role in protective immunity, disease susceptibility, autoimmunity, and drug hypersensitivity, yet the basis of how HLA polymorphism influences T cell receptor (TCR) recognition is unclear. We examined how a natural micropolymorphism in HLA-B44, an important and large HLA allelic family, affected antigen recognition. T cell–mediated immunity to an Epstein-Barr virus determinant (EENLLDFVRF) is enhanced when HLA-B*4405 was the presenting allotype c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 50 publications
8
107
0
Order By: Relevance
“…Specifically, in work by Yu et al (26), it was shown that the HLA-B*57:01 and HLA-B*57:03 subtypes, which differ by only two amino acids, can both present the same HIV-1 Gag KF11 epitope, but with T cell recognition only being observed in the context of HLA-B*57:01. Likewise, a differential recognition of the same EBV epitope by Ag-specific T cells has been observed for three of the HLA-B*44 subtypes (27). Structural studies provide strong evidence that the effect of HLA micropolymorphisms on TCR interaction can in many cases not be predicted by peptide binding studies.…”
Section: Discussionmentioning
confidence: 84%
“…Specifically, in work by Yu et al (26), it was shown that the HLA-B*57:01 and HLA-B*57:03 subtypes, which differ by only two amino acids, can both present the same HIV-1 Gag KF11 epitope, but with T cell recognition only being observed in the context of HLA-B*57:01. Likewise, a differential recognition of the same EBV epitope by Ag-specific T cells has been observed for three of the HLA-B*44 subtypes (27). Structural studies provide strong evidence that the effect of HLA micropolymorphisms on TCR interaction can in many cases not be predicted by peptide binding studies.…”
Section: Discussionmentioning
confidence: 84%
“…Typically, these involve highly related allotypes that exhibit limited sequence differences, which nevertheless often result in biologically significant changes in conformation of the peptide and/or the MHC-I molecule (2,(61)(62)(63). In contrast, despite the comparatively low level of sequence identity between Qa-1 b and HLA-E, remarkably, they present their respective peptide cargoes in a very similar manner for recognition by CD94-NKG2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The orientation of residues Tyr 7 , Met 45 , Glu 63 , and Tyr 159 that line the deep hydrophobic cavity of the P2-binding pocket is similar between both Qa-1 b and HLA-E (Fig. 4B).…”
Section: Qa-1 B Is a Structural Homolog Of Hla-ementioning
confidence: 92%
See 2 more Smart Citations